(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
The spectroscopic properties of lignin solution in DMSO by UV and fluorescent methods have been studied. It has been shown that during dilution of this solution with small quantity of DMSO the intensity of UV absorption increases, while in the fluorescent spectra a new emission peak appears.